Faecal Calprotectin in Treated and Untreated Children With Coeliac Disease and Juvenile Idiopathic Arthritis - Biskou, O.; Gardner-Medwin, J.; Mackinder, M.; Bertz, M.; Clark, C.; Svolos, V.; Russell, R.; Edwards, Christine; McGrogan, P.; Gerasimidis, K. (Lippincott Williams & Wilkins, 2016)
© 2016 by European Society for Pediatric Gastroenterology, Hepatology, and Nutrition and North American Society for Pediatric Gastroenterology,ABSTRACT: This study aimed to provide evidence on whether children at risk of gastrointestinal inflammation have increased measurements of faecal calprotectin (FC). Faecal calprotectin was measured in 232 children; 55 children (n?=?11 treatment naïve) with juvenile idiopathic arthritis (JIA), 63 with coeliac disease (CD); 17 with new diagnosis before and after treatment on gluten free diet and 114 controls. None of the treatment-naive children with JIA had raised FC. Four JIA patients on treatment had a raised FC but in all cases a repeat test was normal. In newly diagnosed CD patients, the median (IQR) FC was higher 36.4 (26–61) than in controls 25.0 (23–41) mg/kg (p?=?0.045) but this significantly decreased 25 (25–25) mg/kg (p?=?0.012) after six months on gluten free diet. Random measurements of FC are not raised in children with JIA or CD. A significant elevation of FC in these groups is not explained by their diagnosis and therefore needs further investigation.